Towards a Philosophy of Liberal Education: John Henry Newman on Teaching Universal Knowledge, the Cultivation of the Intellect, and the Enlargement of Mind - Stewart, Adam (Irish theological quarterly, 2020)
In this essay, I develop a philosophy of liberal education based on an interpretation of Newman's concepts of teaching universal knowledge, the cultivation of the intellect, and the enlargement of mind found in The Idea of a University. I argue that a close reading of Newman's articulation of these three concepts reveals an understanding of the purpose of liberal education as animating truth with reason to produce knowledge that enhances faith and improves society. I also discuss how this philosophy translates into a pedagogy that directly informs my teaching, and, hopefully, contributes to the integration of faith and learning in the lives of my students.